1973
DOI: 10.1136/ard.32.3.272-a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some adrenal steroid hormones on skin fibroblast replication in vitro.

Abstract: We have previously drawn attention to the fact that, in patients suffering from rheumatoid arthritis, the familiar steroid-induced skin-thinning effect which occurs in those given long-term oral corticosteroid medication is absent in those treated with ACTH- (Grahame, 1969). This observation is compatible with the earlier observations of Savage, Copeman, Chapman, Wells, and Treadwell (1962) and West (1961) that 'steroid bruising' is rare in ACTHtreated rheumatoid arthritis patients. This study was undertaken t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…They showed that HDF can synthesize cortisol [ 117 ] and express other important HPA axis factors such as proopiomelanocortin (POMC), adrenocorticotropic hormone (ACTH) [ 107 , 115 , 152 ], and corticotropin releasing hormone (CRH). It has been shown that HDF treatment by cortisol reduces cell proliferation [ 118 , 119 ]. Moreover, HDF express melanocortin receptor 1 (MCR1) [ 109 - 111 , 113 ] as well as CRH receptors [ 108 , 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…They showed that HDF can synthesize cortisol [ 117 ] and express other important HPA axis factors such as proopiomelanocortin (POMC), adrenocorticotropic hormone (ACTH) [ 107 , 115 , 152 ], and corticotropin releasing hormone (CRH). It has been shown that HDF treatment by cortisol reduces cell proliferation [ 118 , 119 ]. Moreover, HDF express melanocortin receptor 1 (MCR1) [ 109 - 111 , 113 ] as well as CRH receptors [ 108 , 114 ].…”
Section: Resultsmentioning
confidence: 99%